Publisher Correction: Insight into the microbial world of Bemisia tabaci cryptic species complex and its relationships with its host - Wang, Hua-Ling; Lei, Teng; Xia, Wen-Qiang; Cameron, Stephen L.; Liu, Yin-Quan; Zhang, Zhen; Gowda, Maruthi M. N.; De Barro, Paul; Navas-Castillo, Jesús; Omongo, Christopher A.; Delatte, Hélène; Lee, Kyeong-Yeoll; et al. (Springer Nature, 2019)
The original version of this Article contained an error in the author list, where Paul De Barro was erroneously removed during publication. In addition, Elvira Fiallo-Olivé was incorrectly affiliated with 'National Crops Resources Research Institute, Namulonge, P.O. Box, 7084, Kampala, Uganda'.